Osteoporosis guidelines on TCM drug therapies: a systematic quality evaluation and content analysis - Zhang, Luan; Li, Jiahui; Xie, Runsheng; Zeng, Lingfeng; Chen, Wenjia; Li, Hui (Frontiers in Endocrinology, 2024)
The aims of this study were to evaluate the quality of osteoporosis guidelines on traditional Chinese medicine (TCM) drug therapies and to analyze the specific recommendations of these guidelines.We systematically collected guidelines, evaluated the quality of the guidelines using the Appraisal of Guidelines Research and Evaluation (AGREE) II tool, and summarized the recommendations of TCM drug therapies using the Patient-Intervention-Comparator-Outcome (PICO) model as the analysis framework.A total of 20 guidelines were included. Overall quality evaluation results revealed that four guidelines were at level A, four at level B, and 12 at level C, whose quality needed to be improved in the domains of "stakeholder involvement", "rigor of development", "applicability" and "editorial independence". Stratified analysis suggested that the post-2020 guidelines were significantly better than those published before 2020 in the domains of "scope and purpose", "stakeholder involvement" and "editorial independence". Guidelines with evidence systems were significantly better than those without evidence systems in terms of "stakeholder involvement", "rigor of development", "clarity of presentation" and "applicability". The guidelines recommended TCM drug therapies for patients with osteopenia, osteoporosis and osteoporotic fracture. Recommended TCM drugs were mainly Chinese patent medicine alone or combined with Western medicine, with the outcome mainly focused on improving bone mineral density (BMD).